Measuring social phobia symptoms in a community sample of adolescents: An examination of the psychometric properties of the SPAI-23 - Apostolakis, Markos; Theodorou, Marios; Neophytou, Klavdia; Panayiotou, Georgia (Frontiers in Psychology, 2022)
A limited number of studies to date have examined subcategories of social fears in adolescents with Social Anxiety (SA). A variety of diagnostic tools has been developed, along with their abbreviated versions, that are used to detect SA but little research has been devoted to the types of fears they each assess. Due to differences in their content, different aspects of SA are addressed and this leads to confusion when the relationship between SA and other constructs is being investigated. The aim of the present study was threefold: a) to contribute to the ongoing debate about specifying subtypes of social fears in youth, which may also relate to disorders subtypes, and address Social Phobia characteristics at that age, b) to examine the psychometric properties of the abbreviated Social Phobia Anxiety Inventory SPAI-23 in Greek-Cypriot adolescents and c) investigate relationships between Social Anxiety and related constructs, verifying the tools convergent and divergent validity. Seven hundred twenty-one adolescent students, (Mean Age: 15.5, 64% female) participated in the study. Participants completed a series of questionnaires, measuring Social Anxiety (SPAI-23), Anxiety Sensitivity (CASI), Psychological Inflexibility (AFQ-Y8), and Behavioral Inhibition (BIS/BAS). Exploratory Factor Analysis on the SPAI-23 revealed a quite similar structure to that of the original questionnaire. Three Social Phobia factors were identified (Performance, Interaction & Presence in a social context) and one agoraphobia factor after the evaluation of alternative solutions. Findings were verified by means of Confirmatory Factor Analysis, testing alternative models. As was expected, all Social Phobia factors were positively correlated with Psychological Inflexibility, Behavioral Inhibition and Anxiety Sensitivity. Findings were in line with recent evidence on clinical youth samples, and contribute to significant insights towards offering sophisticated and personalized assessment and interventions.